Toughened phenolic foam material and preparation method thereof
Through the synergistic action of furfural and polyvinyl alcohol, the cross-linking density and toughness of phenolic foam materials are improved, and the problems of embrittlement and poor bending strength of existing materials are solved, thereby achieving higher material performance.
Patent Information
- Application Number
- CN202411559326.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing phenolic foam materials have problems such as high brittleness, easy powder loss, and poor bending strength, which limits its further promotion and application.
Through the synergistic action of furfural and polyvinyl alcohol, the cross-linking density of phenolic resin is adjusted, the cross-linking density of the curing process is improved, and the long-chain polyvinyl alcohol is introduced to improve the toughness and strength of the foam material.
It effectively improves the brittleness and powder loss problems of phenolic foam materials, improves its bending strength and toughness, and enhances the overall performance of the material.
Abstract
Description
Technical Field
[0001] This invention relates to the field of phenolic foam materials technology, specifically to a toughened phenolic foam material and its preparation method. Background Technology
[0002] Phenolic foam is a thermal insulation material with excellent thermal insulation, flame retardancy, low smoke, low toxicity, heat resistance, and chemical corrosion resistance. The rigid benzene ring structure of phenolic molecules makes phenolic foam dimensionally stable, and it is widely used in large cold storage facilities, tanks, ships, various insulated pipes, and the construction industry. However, the methylene groups on the phenolic resin structure cause the rigid aromatic rings to be tightly packed, hindering internal rotation and resulting in a high degree of cross-linking. Consequently, foam materials made from phenolic resin suffer from problems such as high brittleness, easy powdering, and poor flexural strength, which restricts the further promotion and application of phenolic foam materials.
[0003] Therefore, it is necessary to improve the existing phenolic foam technology. Summary of the Invention
[0004] One of the objectives of this invention is to overcome the defects in the prior art and provide a toughened phenolic foam material. Through the synergistic effect of furfural and polyvinyl alcohol, the strength of the foam material is guaranteed while its toughness is further improved, thereby improving the defects of phenolic foam material such as embrittlement and easy powdering.
[0005] To achieve the above-mentioned process effects, the technical solution of the present invention is: a toughened phenolic foam material, the main components of which are modified resin substrate and foaming aid;
[0006] The modified resin substrate includes modified phenolic resin and an aqueous solution of polyvinyl alcohol;
[0007] The foaming aids include surfactants, foaming agents, and acid curing catalysts;
[0008] The modified phenolic resin is polymerized from phenol, furfural, and formaldehyde under the action of an alkali agent.
[0009] The mass fraction of the polyvinyl alcohol aqueous solution is 5% to 8%;
[0010] The amount of the polyvinyl alcohol aqueous solution added is 15% to 30% of the mass of the undehydrated modified phenolic resin.
[0011] The preferred technical solution is that, by weight, the main components of the foaming raw material include 100 parts of modified resin substrate, 2-10 parts of surfactant, 3-20 parts of foaming agent, and 5-30 parts of acid curing catalyst.
[0012] A preferred technical solution is that the mass of furfural is 10% to 20% of the total mass of phenol, and the molar ratio of phenol to formaldehyde is 1:(1.2 to 2.5).
[0013] A preferred technical solution is that the modified phenolic resin has an average molecular weight of 800-1200, the modified resin substrate has a water content of 6%-12%, and the modified substrate has a viscosity of 4500-8000 mPa·s.
[0014] A preferred technical solution is that the alkaline agent is one or a combination of two or more of sodium hydroxide, potassium hydroxide, and barium hydroxide.
[0015] A preferred technical solution is that the foaming agent includes pentane and fluorinated olefins, and the acid curing catalyst is one or a combination of two or more of xylenesulfonic acid, phenolsulfonic acid and p-toluenesulfonic acid.
[0016] A preferred technical solution is that the foaming raw material further includes urea, and the urea accounts for 2% to 10% of the mass fraction of the modified resin substrate.
[0017] The second objective of this invention is to overcome the deficiencies in the prior art and provide a method for preparing toughened phenolic foam material, comprising the following steps:
[0018] S1: Phenol and furfural are mixed and reacted under the action of a first alkali agent with a first heating reaction to obtain an addition mixture;
[0019] S2: After the addition mixture cools down, formaldehyde is slowly added, and the reaction is heated a second time to obtain a condensation mixture;
[0020] S3: After the polycondensation mixture is adjusted to neutral and cooled, an aqueous solution of polyvinyl alcohol is added, and the mixture is dehydrated at a temperature below the polycondensation temperature to obtain a modified resin substrate;
[0021] S4: A modified resin substrate is mixed with a foaming agent to obtain a foaming raw material, which is then sprayed onto the substrate to foam and cure simultaneously.
[0022] The preferred technical solution is as follows: the temperature of the first heating is 60-70℃, and the heat preservation reaction time is 45-70 min; in step S2, the temperature is lowered to 40-50℃, and formaldehyde is added; the temperature of the second heating is 85-95℃, and the heat preservation reaction time is 90-150 min; in step S4, the foaming and curing temperature is 60-80℃, and the time is 10-30 min.
[0023] A preferred technical solution is that the pH in S1 under the action of the first alkali is 9-11; and the pH in S2 under the action of the second alkali is 8-10.
[0024] The advantages and beneficial effects of this invention are as follows:
[0025] This phenolic foam material utilizes the synergistic effect of furfural and polyvinyl alcohol. The former regulates the crosslinking density of the phenolic resin and provides more active groups during foaming and curing, thereby increasing the crosslinking density during the curing process. The latter, long-chain polyvinyl alcohol, ensures the strength of the foam material while further improving its toughness, thus improving defects such as brittleness and easy powdering of phenolic foam materials. Detailed Implementation
[0026] The specific embodiments of the present invention will be further described below with reference to examples. These examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0027] The foaming raw material of phenolic foam material
[0028] The basic components of foaming raw materials include modified resin base material, foaming agent, and acid curing catalyst. Other functional additives such as surfactants, toughening agents, smoke suppressants, flame retardants, and fillers known in phenolic foaming raw materials can also be selectively added to give the foam corresponding functions.
[0029] foaming agent
[0030] The foaming agent can be a known phenolic resin foaming agent. Commonly used foaming agents are hydrocarbons with C6 or less, including saturated hydrocarbons, unsaturated hydrocarbons, and hydrocarbons containing substituent groups.
[0031] Blowing agents include pentane and fluorinated olefins. Furthermore, to improve the thermal insulation performance and stability of phenolic resin foam, cyclopentane is a preferred blowing agent. Further, to reduce the thermal conductivity and stability of the foam, preferred blowing agents include monochlorotrifluoropropane, (cis)-1,1,1,4,4,4-hexafluoro-2-butene, 1-chloro-3,3,3-trifluoropropene, and 1-chloro-2,3,3-trifluoropropene, which offer more significant improvements in thermal conductivity.
[0032] Furthermore, in order to achieve both good thermal insulation properties and thermal conductivity in the foam, resulting in a low-density and stable foam, the weight ratio of cyclopentane to fluorinated olefins is (2-4):1. Even further, the weight ratio of cyclopentane to fluorinated olefins is (2-3):1.
[0033] surfactants
[0034] The surfactant reduces the surface tension of the liquid resin, giving the foaming material a good interfacial orientation. The surfactant is a known surfactant used for phenolic resin foaming, including but not limited to polysiloxanes, polyoxyethylene ethers, and polytriglycerides. Preferably, the surfactant is one or a combination of two or more selected from Tween-80, castor oil polyoxyethylene ether, and alkylphenol polyoxyethylene ether.
[0035] Acid-curing catalyst
[0036] The acid curing catalyst can be any known acid used in phenolic resin foaming materials, including but not limited to inorganic acids such as phosphoric acid and sulfuric acid, and organic acids such as p-toluenesulfonic acid, benzenesulfonic acid, oxalic acid, carbonic acid, and methanesulfonic acid. Since inorganic acids react more readily with metals under humid conditions, the preferred acid curing catalyst is one or a combination of two or more selected from xylenesulfonic acid, phenolsulfonic acid, and p-toluenesulfonic acid.
[0037] Inorganic packing
[0038] The role of inorganic fillers is to preferentially react with the acid-curing catalyst. The range of inorganic fillers includes metal oxides, metal carbonates, and metal hydroxides, such as alumina, zinc oxide, calcium carbonate, magnesium carbonate, and magnesium hydroxide. Furthermore, alumina and / or calcium carbonate are preferred inorganic fillers, as they not only reduce residual acidity but also have minimal impact on foam performance.
[0039] Modified resin substrate
[0040] By controlling the temperature and pH of the reaction solution, phenol and furfural are first mixed for addition reaction. By controlling the mass ratio of the two, an addition mixture with predominantly mono- and di-substituted compounds is obtained. Then, after cooling, formaldehyde is added for further substitution, and the pH is adjusted to be suitable for the addition reaction of formaldehyde with phenol and phenol with different substitution amounts. Finally, the temperature is raised to carry out the condensation reaction. Among these, furfural has a larger molecular weight than formaldehyde and greater steric hindrance; an increased pH value is conducive to the addition reaction of furfural with phenol.
[0041] Because furfural contains a furan ring, the resulting addition mixture is sterically hindered during polycondensation, which reduces the crosslinking density of the polycondensation. This, in turn, retains the hydroxymethyl active groups that can be further reacted, as well as the active hydrogen atoms at the α position on the furan ring. This is beneficial for crosslinking with polyvinyl alcohol and other polymers with hydroxymethyl active groups during the foaming and curing process under the action of an acidic catalyst to form a foam layer that is tough and maintains strength.
[0042] When polyvinyl alcohol (PVA) aqueous solution is added, the polycondensation mixture has already completed the reaction. Therefore, the PVA in the PVA aqueous solution still contains hydroxyl groups that can participate in the reaction. If the mass fraction of the PVA aqueous solution is too high, the viscosity will be high, which is not conducive to uniform mixing; if the mass fraction is too low, although the compatibility with the polycondensation mixture is improved, the increased water content will make the dehydration process difficult and energy consumption high.
[0043] Dehydration conditions: Under vacuum conditions, the dehydration temperature is 40-50℃.
[0044] Preparation of polyvinyl alcohol aqueous solution
[0045] Water and polyvinyl alcohol were mixed in a specific ratio and stirred at 85°C for 60 minutes. Furthermore, the molecular weight of polyvinyl alcohol was 1700–1800.
[0046] Foam parts made of phenolic foam material
[0047] Phenolic foam can be used to manufacture related products, including but not limited to structural components, sheets, rolls, and covered products with predetermined structural shapes. Furthermore, the foam can be composite-foamed with metal foil, color-coated steel, non-woven fabric, and fiberglass cloth to create composite products in which the foam and the aforementioned materials are integrally connected.
[0048] Example 1
[0049] The preparation method of toughened phenolic foam material includes the following steps:
[0050] S1: 100g phenol and 18g furfural are mixed, the pH is adjusted to 10 with the first alkali agent, and the temperature is raised to 65℃ for 60min to obtain an addition mixture;
[0051] S2: After the addition mixture is cooled to 45°C, formaldehyde is slowly added. The molar mass ratio of formaldehyde to phenol is 1.8:1. The second alkali agent is used to adjust the pH value to 9. The temperature is increased to 90°C at 1°C / min and the reaction time is kept at 2h to obtain the polycondensation mixture.
[0052] S3: After the obtained polycondensation mixture is adjusted to neutral and cooled, a 6% (w / w) aqueous solution of polyvinyl alcohol is added, and the mixture is dehydrated at a temperature below the polycondensation temperature to obtain a modified resin substrate. The amount of polyvinyl alcohol aqueous solution added is 20% of the mass of the undehydrated modified phenolic resin. The average molecular weight of the modified phenolic resin is 950, the water content of the modified substrate is 11%, and the viscosity of the modified substrate is 5500 mPa·s.
[0053] S4: A foaming raw material is obtained by mixing a modified resin substrate with a foaming agent. The foaming raw material is sprayed onto the substrate and foams and cures simultaneously. The foaming and curing temperature is 70℃ and the time is 20min. The main components of the foaming raw material, by mass, include 100 parts of modified substrate, 4 parts of sesame oil polyoxyethylene ether, 10 parts of cyclopentane / 1-chloro-2,3,3-trifluoropropylene (weight ratio 60 / 40), 15 parts of dimethylbenzenesulfonic acid / phenolsulfonic acid (weight ratio 50 / 50), and 5 parts of urea.
[0054] Example 2
[0055] Example 2 is based on Example 1, except that in S1, 100g of phenol and 10g of furfural are mixed. Other components and proportions remain unchanged, and the process conditions remain unchanged.
[0056] Example 3
[0057] Example 3 is based on Example 1, except that in S1, 100g of phenol and 20g of furfural are mixed. Other components and proportions remain unchanged, and the process conditions remain unchanged.
[0058] Example 4
[0059] Example 4 is based on Example 1, except that in S1, 100g of phenol is mixed with 5g of furfural. Other components and proportions remain unchanged, as do the process conditions.
[0060] Example 5
[0061] Example 5 is based on Example 1, except that in S1, 100g of phenol is mixed with 24g of furfural. Other components and proportions remain unchanged, as do the process conditions.
[0062] Example 6
[0063] Example 6 is based on Example 1, except that the amount of polyvinyl alcohol aqueous solution added is 15% of the mass of the undehydrated modified phenolic resin. The water content of the modified substrate is 10%, and the viscosity of the modified substrate is 5000 mPa·s.
[0064] Example 7
[0065] Example 7 is based on Example 1, except that the amount of polyvinyl alcohol aqueous solution added is 25% of the mass of the undehydrated modified phenolic resin. The water content of the modified substrate is 13%, and the viscosity of the modified substrate is 5800 mPa·s.
[0066] Example 8
[0067] Example 8 is based on Example 1, except that steps S1 and S2 are combined into one step, namely, phenol, furfural and formaldehyde are mixed, the pH is adjusted to 9-10, the reaction is carried out at 65°C for 60 minutes, and then the temperature is raised to 90°C for 2 hours.
[0068] Example 9
[0069] Example 9 is based on Example 1, except that in S1, the reaction time for preparing the addition mixture is 40 min. Other components and proportions remain unchanged, as do the process conditions.
[0070] Example 10
[0071] Example 10 is based on Example 1, except that in S1, the reaction time for preparing the addition mixture is 80 min. Other components and proportions remain unchanged, as do the process conditions.
[0072] Example 11
[0073] Example 11 is based on Example 1, except that in S2, the reaction time for obtaining the polycondensation mixture is 100 min. Other components and proportions remain unchanged, and the process conditions remain unchanged.
[0074] Example 12
[0075] Example 12 is based on Example 1, except that in S2, the reaction time for obtaining the polycondensation mixture is 140 min. Other components and proportions remain unchanged, as do the process conditions.
[0076] Comparative Example 1
[0077] Comparative Example 1 is based on Example 1, except that the modified resin substrate does not contain an aqueous solution of polyvinyl alcohol. Other components and proportions remain unchanged, as do the process conditions.
[0078] Comparative Example 2
[0079] Comparative Example 2 is based on Example 1, except that the modified phenolic resin is polymerized from phenol and formaldehyde under the action of an alkali agent, i.e., step S1 is not included. Other components and proportions remain unchanged, and the process conditions remain unchanged.
[0080] Performance testing
[0081] (1) Foam density: The apparent density of thermal insulation products in the building sector is determined according to GB / T 6343 standard;
[0082] (2) Compressive strength: According to GB / T 8813 standard, the compressive stress of rigid foam plastic with a relative deformation of 10% is measured;
[0083] (3) Bending strength: The load value at which rigid foam plastic breaks is determined according to GB / T 8812.1 standard;
[0084] The test results of the examples and comparative examples are shown in the table below:
[0085] Sample <![CDATA[Density / kg / m 3 > Bending strength / N Compressive strength / kPa Example 1 50.9 85 190 Example 2 51.2 74 178 Example 3 50.4 81 186 Example 4 51.4 60 170 Example 5 49.5 79 182 Example 6 50.5 80 183 Example 7 51.6 76 175 Example 8 51.0 56 150 Example 9 51.3 75 177 Example 10 50.1 72 173 Example 11 50.2 70 168 Example 12 51.5 73 172 Comparative Example 1 50.6 50 142 Comparative Example 2 51.1 45 130
[0086] Compared to Example 1, in Example 4, the content of furfural in the addition reaction of the modified phenolic resin was too small, the crosslinking density of the polycondensation reaction was still very large, the toughness was not significantly improved, resulting in low flexural strength and compressive strength.
[0087] Compared to Example 1, Example 5 shows that the modified phenolic resin has an excessive amount of furfural in the addition reaction, which leads to a decrease in the crosslinking density of the polycondensation reaction and has a negative impact on the toughness, flexural strength and compressive strength of the phenolic foam material.
[0088] Compared to Example 1, Example 7 shows that the amount of polyvinyl alcohol aqueous solution added is increased, the resin viscosity increases after dehydration, foaming becomes difficult, and it has a negative impact on toughness, flexural strength and compressive strength.
[0089] Compared to Example 1, in Example 8, furfural and formaldehyde were added simultaneously and reacted with phenol. The crosslinking density of the polycondensation reaction was still very high, and the improvement in toughness was not obvious. Moreover, at a temperature of 65°C, the active hydrogen of phenol was easily replaced by addition and polycondensation, making it difficult to form high-strength foam material during the foaming process, resulting in a decrease in both flexural strength and compressive strength.
[0090] Compared to Example 1, in Examples 9 and 10, the addition reaction time of furfural and phenol in S1 was either too short or too long, which disrupted the balance of crosslinking density of the polycondensation mixture and had a negative impact on both flexural strength and compressive strength.
[0091] Compared to Example 1, Example 11 shows that the polycondensation reaction time is shortened, the resulting polycondensation mixture has high activity but low molecular weight, and the foamed material produced by foaming is not strong enough, thus having a negative impact on toughness, flexural strength and compressive strength.
[0092] Compared to Example 1, Example 12 showed that the polycondensation reaction time was prolonged, resulting in increased viscosity and decreased activity of the polycondensation mixture, which was not conducive to foaming and led to a decrease in both flexural strength and compressive strength.
[0093] Compared to Example 1, Comparative Examples 1 and 2 show that furfural improves the crosslinking structure of the polycondensation mixture, and polyvinyl alcohol aqueous solution improves the crosslinking structure during the foaming polymerization process. Both furfural modification and polyvinyl alcohol aqueous solution modification are indispensable, and their synergistic effect improves the toughness and strength of the phenolic foam material.
[0094] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A toughened phenolic foam material, characterized in that: The main components of its foaming raw materials are modified resin base material and foaming auxiliary agent; The modified resin substrate includes a modified phenolic resin and a polyvinyl alcohol aqueous solution; The foaming aid comprises a surfactant, a foaming agent, and an acid curing catalyst; The modified phenolic resin is polymerized by phenol, furfural and formaldehyde under the action of an alkali agent; The mass fraction of the polyvinyl alcohol aqueous solution is 5% to 8%; The amount of the polyvinyl alcohol aqueous solution added is 15% to 30% of the mass of the undehydrated modified phenolic resin.
2. The toughened phenolic foam material according to claim 1, characterized in that: Calculated by weight, the main components of the foaming raw material include 100 parts of modified resin substrate, 2 to 10 parts of surfactant, 3 to 20 parts of foaming agent, and 5 to 30 parts of acid curing catalyst.
3. The toughened phenolic foam material according to claim 1 or 2, characterized in that: The mass of the furfural is 10% to 20% of the total mass of phenol, and the molar ratio of the phenol to formaldehyde is 1:(1.2 to 2.5).
4. The toughened phenolic foam material according to claim 1 or 2, characterized in that: The average molecular weight of the modified phenolic resin is 800-1200, the water content of the modified resin substrate is 6%-12%, and the viscosity of the modified substrate is 4500-8000 mPa•s.
5. The toughened phenolic foam material according to claim 1, characterized in that: The alkaline agent is one or a combination of two or more of sodium hydroxide, potassium hydroxide and barium hydroxide.
6. The toughened phenolic foam material according to claim 1, characterized in that: The foaming agent includes pentane and fluorine-substituted olefins, and the acid curing catalyst is one or a combination of two or more of xylene sulfonic acid, phenol sulfonic acid and p-toluene sulfonic acid.
7. The toughened phenolic foam material according to claim 1, characterized in that: The composition of the foaming raw material also includes urea, and the mass fraction of the urea in the modified resin substrate is 2% to 10%.
8. A method for preparing a toughened phenolic foam material, characterized in that: The following steps are involved: S1: Phenol and furfural are mixed and reacted for the first time at elevated temperature under the action of the first alkali agent to obtain an addition mixture; S2: After the addition mixture is cooled, formaldehyde is slowly added, and the temperature is raised for a second time to obtain a polycondensation mixture; S3: After the polycondensation mixture is adjusted to neutral and cooled, a polyvinyl alcohol aqueous solution is added, and dehydration is performed at a temperature lower than the polycondensation temperature to obtain a modified resin substrate; S4: The modified resin substrate is mixed with a foaming aid to obtain a foaming raw material, and the foaming raw material is sprayed on the substrate to foam and solidify at the same time.
9. The method for preparing a toughened phenolic foam material according to claim 7, characterized in that: The temperature of the first heating is 60-70°C, and the insulation reaction time is 45-70 minutes; the temperature in S2 is lowered to 40-50°C, and formaldehyde is added; the temperature of the second heating is 85-95°C, and the insulation reaction time is 90-150 minutes; The foaming and curing temperature in S4 is 60-80° C. and the time is 10-30 min.
10. The method for preparing a toughened phenolic foam material according to claim 7, characterized in that: The pH of S1 under the action of the first alkali agent is 9-11; the pH of S2 under the action of the second alkali agent is 8-10.